Higher hemoglobin A1C and atherogenic lipoprotein profiles in children and adolescents with type 2 diabetes mellitus - Pelham, James Heath (J Clin Transl Endocrinol, 2018)
AIM: Significant knowledge gaps exist regarding lipoprotein profiles in children with type 2 diabetes mellitus (T2DM). The primary objective was to analyze the type and nature of lipoprotein abnormalities present in children with T2DM and to identify determinants of adverse lipoprotein profiles. The secondary objective was to assess associations with elevated glycated hemoglobin (HbA1C), i.e., <8% vs. ≥8.0% and pediatric dyslipidemias in the setting of T2DM. METHODS: This retrospective chart review included children with T2DM who had undergone lipoprotein analysis and were not on lipid lowering medications (n = 93). RESULTS: The participants (mean age 15.2 ± 2.7y) were 71% female and 78% African American (AA). Adjusted for age, sex, and race, BMI z-score was positively associated with LDL-pattern B (pro-atherogenic profile with small dense LDL particles) (P = 0.01), and negatively associated with total HDL-C (P = 0.0003). HbA1C was robustly positively associated with the LDL-C, apoB and LDL pattern B (all P < 0.001). Patients with an HbA1C >8% had significantly higher total cholesterol (191.4 vs. 158.1 mg/dL, P = 0.0004), LDL-C (117.77 vs. 92.3 mg/dL, P = 0.002), apoB (99.5 vs. 80.9 mg/dL, P = 0.002), non-HDL-C (141.5 vs. 112.5, P = 0.002), and frequency of LDL pattern B (57% vs. 20%, P = 0.0008). CONCLUSION: HbA1C and BMI were associated with adverse lipoprotein profiles, and may represent two major modifiable cardiovascular risk factors in the pediatric T2DM population. Patients with an HbA1C higher than 8.0% had significantly worse atherogenic lipid profile, i.e., higher LDL-C, non-HDL-C, apoB and LDL pattern B, suggesting adequate glycemia may improve adverse lipoprotein profiles.